Changes in normal speech after fatiguing the tongue. - Solomon, Nancy Pearl (Journal of Speech, Language & Hearing Research, 2000)
Detrimental effects of tongue fatigue on speech have been assumed to exist based on neuromotor speech disorders. However, to address whether fatigue is a contributing cause to impaired speech requires an experimental protocol with an uncomplicated population. This study induced tongue fatigue in eight neurologically normal persons and examined changes in speech perceptually and acoustically. The fatigue task consisted of repeated cycles of 6 s of sustained maximum voluntary contraction and 4 s of rest until 50IX% of maximum strength could not be achieved for three consecutive cycles. Participants then produced speech that was weighted heavily with lingual-palatal consonants. Perceptual analyses of the speech revealed a statistically significant deleterious effect of induced tongue fatigue on speech precision and an incomplete reversal of this effect after a recovery period. Acoustically, the first and third spectral moments (mean and skewness) of the spectral energy for /t/, /s/, and /IMI/ differed significantly after fatigue but in directions opposite to a priori predictions. Tendencies were found for decreased stop-closure duration and increased voice onset time for /t/ after fatigue. Supplemental analyses revealed decreased second formant (F2) frequency for /u/ and /i/ and flattened F2 transition for the diphthong /ITSI/ after fatigue. These results indicate disruption of tongue positioning and transitioning for lingual-palatal consonants during speech after prolonged strenuous tongue exercises. Reprinted by permission of the publisher. Reprinted by permission of the publisher.